2021
DOI: 10.1039/d0ee03203d
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-assisted large-scale synthesis of graphene microspheres for superior potassium-ion batteries

Abstract: Large-scale low-cost preparation methods for high quality graphene are critical for advancing graphene-based applications in energy storage, and beyond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(109 citation statements)
references
References 50 publications
1
104
0
Order By: Relevance
“…Except for carbon modification and nanostructure design, heteroatom doping is also an effective strategy to boost electrochemical performance by adjusting the electronic/ionic states of the target, leading to enhanced adsorption ability, lower diffusion barrier, and improved intrinsic electronic/ionic conductivity in electrode materials (Figure 5c). [ 65,66 ] Numerous heteroatom doped carbonaceous materials have been applied as building blocks to construct heterostructures, in which the heteroatom provides additional active sites to bond with other building blocks, improving the electronic conductivity and structural durability of electrode materials. Nevertheless, heteroatom doped non‐carbon materials are rarely discussed in previous researches.…”
Section: Design Strategies Of Heterostructures For Energy Storage Applicationsmentioning
confidence: 99%
“…Except for carbon modification and nanostructure design, heteroatom doping is also an effective strategy to boost electrochemical performance by adjusting the electronic/ionic states of the target, leading to enhanced adsorption ability, lower diffusion barrier, and improved intrinsic electronic/ionic conductivity in electrode materials (Figure 5c). [ 65,66 ] Numerous heteroatom doped carbonaceous materials have been applied as building blocks to construct heterostructures, in which the heteroatom provides additional active sites to bond with other building blocks, improving the electronic conductivity and structural durability of electrode materials. Nevertheless, heteroatom doped non‐carbon materials are rarely discussed in previous researches.…”
Section: Design Strategies Of Heterostructures For Energy Storage Applicationsmentioning
confidence: 99%
“…In our group, for the full cell study, we have used conventional CR2032‐type two‐electrodes coin cell and novel three‐electrodes cell. From the literature, we found that commonly used cathode materials for full cell were Prussian blue, layered metal oxides, polyanionic compounds, and organic materials [39,127–130] . Their counterpart anode materials were mainly carbonaceous materials, metallic alloy type materials, and others [6,131–137] .…”
Section: Full Cell Designmentioning
confidence: 99%
“…[ 2 ] However, LIBs are trapped by scarce reserves (≈0.0017 wt%), high costs and safety issues. [ 3 ] Therefore, it is urgent to develop novel generation EES devices, [ 4 ] such as sodium‐ion batteries (SIBs), [ 5 ] potassium‐ion batteries (PIBs), [ 6 ] zinc‐ion batteries (ZIBs), [ 7 ] magnesium‐ion batteries (MIBs), [ 8 ] calcium‐ion batteries (CIBs), [ 9 ] aluminum‐ion batteries (AIBs), [ 10 ] dual‐ion batteries (DIBs), [ 11 ] and solid‐state batteries (SSBs), [ 12 ] etc.…”
Section: Introductionmentioning
confidence: 99%